2016
DOI: 10.1016/j.cub.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

translin Is Required for Metabolic Regulation of Sleep

Abstract: Summary Dysregulation of sleep or feeding has enormous health consequences. In humans, acute sleep loss is associated with increased appetite and insulin insensitivity, while chronically sleep-deprived individuals are more likely to develop obesity, metabolic syndrome, type II diabetes, and cardiovascular disease. Conversely, metabolic state potently modulates sleep and circadian behavior; yet, the molecular basis for sleep-metabolism interactions remains poorly understood. Here, we describe the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 48 publications
5
113
1
Order By: Relevance
“…Thus, we used the trsn mutants to further test whether the sleep increase after starvation might be due to sleep loss during starvation. In support of the study of Murakami et al (2016), we found that trsn mutants, unlike their wild-type controls, fail to decrease their sleep during starvation (Fig. 2B and C).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Thus, we used the trsn mutants to further test whether the sleep increase after starvation might be due to sleep loss during starvation. In support of the study of Murakami et al (2016), we found that trsn mutants, unlike their wild-type controls, fail to decrease their sleep during starvation (Fig. 2B and C).…”
Section: Resultssupporting
confidence: 84%
“…A recent study has shown that trsn fly mutants fail to show starvation-induced sleep suppression while preserving homeostatic feeding strategies, such as increased food intake, after starvation (Murakami et al, 2016). Thus, we used the trsn mutants to further test whether the sleep increase after starvation might be due to sleep loss during starvation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that ingested protein promotes both sleep and wakefulness, and that the wakefulness is normally counterbalanced by Lkr neuronal activity. While this study does not specifically identify the waking output for protein, it was previously shown that Translin acts through Lk-expressing cells to drive wakefulness in response to sucrose starvation (Murakami et al, 2016). While this does not explain rapid wake promotion in response to protein ingestion, it does demonstrate that Lk-expressing cells are capable of promoting wakefulness.…”
Section: Discussionmentioning
confidence: 99%